2020
DOI: 10.3758/s13415-020-00807-3
|View full text |Cite
|
Sign up to set email alerts
|

What you want may not be what you like: A test of the aberrant salience hypothesis in schizophrenia risk

Abstract: Motivational abnormalities represent a key area of dysfunction in individuals with, or at risk for, schizophrenia and severely limit broad domains of functioning in these populations. The aberrant salience hypothesis posits that motivational abnormalities are the result of an over-attribution of salience to nonpleasurable stimuli but an under-attribution of salience to pleasurable ones. Consequently, people "want" what they do not "like" but do not "want" what they "like." However, it is unclear how this hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 64 publications
1
3
0
Order By: Relevance
“…In the current study, and consistent with previous research (Kwapil et al, 2012; Li et al, 2019; Li et al, 2020; Martin et al, 2020), individuals met the criteria for the SocAnh group if they had an elevated score on the brief RSAS (>1.5 SD above the mean) but not on the brief PAS or MIS (<1.5 SD above the mean). Individuals met the criteria for the PerMag group if they had elevated scores on the brief PAS or MIS (>1.5 SD above the mean on either scale) but not on the brief RSAS (<1.5 SD above the mean).…”
Section: Methodssupporting
confidence: 86%
“…In the current study, and consistent with previous research (Kwapil et al, 2012; Li et al, 2019; Li et al, 2020; Martin et al, 2020), individuals met the criteria for the SocAnh group if they had an elevated score on the brief RSAS (>1.5 SD above the mean) but not on the brief PAS or MIS (<1.5 SD above the mean). Individuals met the criteria for the PerMag group if they had elevated scores on the brief PAS or MIS (>1.5 SD above the mean on either scale) but not on the brief RSAS (<1.5 SD above the mean).…”
Section: Methodssupporting
confidence: 86%
“…The aberrant processing of these informative or relevant (i.e., salient) events, as seen in blunted prediction errors to rewards (see Prediction Error Signaling in Psychosis ) ( 45 , 46 ) or decreased responses to relevant visual stimuli ( 38 , 47 ), seem to relate to negative symptoms, such as anhedonia or lack of motivation ( 47 , 48 , 49 , 50 ). In contrast, aberrant processing of irrelevant (i.e., nonsalient) events, such as neutral events in reward learning or oddball paradigms, seems to provide an explanation for positive symptoms ( 33 , 34 ). We do note, however, some studies with contradictory symptom associations [e.g., ( 25 , 27 , 51 )].…”
Section: Salience Processing In Psychosismentioning
confidence: 96%
“…Furthermore, overweighting nonpredictive cues was correlated with more severe positive symptom scores in schizophrenia ( 33 ). A recent study ( 34 ) exploring neutral stimuli in a reward learning setting showed that individuals with psychotic-like experiences overattribute salience to neutral stimuli and underattribute salience to rewards, indicating that abnormal salience attribution is a trait-like feature. Together, these studies show that neutral or irrelevant stimuli are consistently overweighted in patients at different disease stages, with the exception of patients with treatment-resistant schizophrenia, showing a clear indication of aberrant salience, although associations with symptoms are inconsistent.…”
Section: Salience Processing In Psychosismentioning
confidence: 99%
“…Each item is answered True (1) or False (0), and a total RSAS score is calculated as the sum of all individual items (possible range=0-15). The RSAS exhibits adequate psychometric properties 64,94,95 and is widely used in the SA 63 , SSD 53 , and psychosis risk literature 96,97 . In our sample, omega was 0.91.…”
Section: Daily Diarymentioning
confidence: 99%